(untitled) (KULT_online, 2018)
This interrogation into the challenges and politics involved in specifying ‘the contemporary’ demonstrates that the plight of ‘naming the now’ is highly complex, never complete, and nonetheless well worth our while. Through close analyses of five literary and filmic genres, Theodore Martin proposes an innovative approach to historicizing the present through the lens of genre and generic change. This proposed path to understanding the present is particularly relevant for literary and film studies students and scholars interested in genre theory and contemporary cultural artifacts. However, anyone employing the term ‘contemporary’ without further reflection will find compelling reasons and inspiration in Contemporary Drift for adopting more nuanced approaches.